Blended Learning Model for Improving Learning Effectiveness on Techniques of Refrigeration and Air Conditioning Course - Hartoyo Hartoyo (LPPM UNY, 2011)
This article was aimed at examining the effectiveness of the blended learning model, namely the combination of face-to-face learning and web-based e-learning. The study was classroom action research. The subjects were students who took the Technique of Refrigeration and Air Conditioning Course in the second half of the Year 2008/2009. Methods of data collection were questionnaire, observation, and tests. Data were analyzed descriptively. The findings of this study were: (1) blended learning model can improve the effectiveness of the learning process: make learning fun and challenging, able to increase enthusiasm, improve students’ involvement, provide a conducive learning athmosphere, make learning more meaningful, and increase learning flexibility (with a mean score of 3.096 and 3.219 of a score range of 1-4 respectively for the cycle I and II); (2)Learning achievement increases, all students can achieve and exceed the minimum criteria (B-). Cycle I: The score of A= 3 people (18.75%), score A-= one person (6.25%), score B+= 4 people (25%), score B= 5 students (31.25%), and the B-= 3 people (18.75%). Cycle II: The score of A= 4 people (25%), score A-= 5 people (31.25%, score B+= 1 person (6.25%), and the B= 6 people (37.50%).